A Brief Review on the Conformal Scalar Equation - Cerver´o, Jos´e M. (European Journal of Applied Sciences, 2024)
In this short note we develop a method to fully integrate the conformal scalar equation in dimensions (N −1, 1) where N is the total number of dimensions. The Conformal Group in this flat space is SO(N, 2) and the Conformal Scalar equation is readily given by [1]: